Efektifitas LKPD berbasis problem based learning untuk meningkatkan literasi sains siswa pada materi pemanasan global - Asma Sidik, Mutia; Latip, Abdul; Rahmaniar, Andinisa (Universitas Garut, 2025)
The Effectiveness of LKPD based on Problem Based Learning to Improve Students' Science Literacy on Global Warming Materials. One of the skills that students must have in the 21st century is science literacy skills. However, based on data, the science literacy of Indonesian students is relatively low. With that, it is necessary to improve the quality of learning, one of which is the use of teaching materials such as LKPD (Student Worksheet). This study aims to determine the effectiveness of PBL-based LKPD in improving students' science literacy. Furthermore, the method applied is Pre-experimental with a One Group Pretest-Posttest design. The research sample used was classes VII-D which amounted to 35 students in junior high schools in Garut Regency. The instruments used in this study were in the form of science literacy-based questions as many as 21 multiple-choice questions. The data analysis used was in the form of N-Gain score calculation to determine the effectiveness of PBL-based LKPD. The results obtained show that PBL-based LKPD has high effectiveness in improving science literacy in aspects of science knowledge and science competence. Furthermore, the results of the calculation on content knowledge obtained a high category N-Gain with a score of 0.83, then the epistemic knowledge indicator obtained a moderate category N-Gain with a score of 0.74, and procedural knowledge obtained a medium category with a score of 0.57. Meanwhile, the indicator explains that the scientific phenomenon obtained an N-Gain result of 0.48 with the medium category, and for the indicator to interpret data and facts scientifically of 0.58 (medium category). Thus, results were obtained that showed that PBL-based LKPD has the effectiveness of increasing science literacy on global warming materials. Key word: Science Literacy, LKPD, Pemanasan Global, Problem Based Learning